Why iPlay: The Relationships of Autistic and Schizotypal Traits With Patterns of Video Game Use - Yang, Nancy; Hurd, Pete L.; Crespi, Bernard J. (Frontiers in Psychology, 2022)
Video games are popular and ubiquitous aspects of human culture, but their relationships to psychological and neurophysiological traits have yet to be analyzed in social-evolutionary frameworks. We examined the relationships of video game usage, motivations, and preferences with autistic and schizotypal traits and two aspects of neurophysiology, reaction time and targeting time. Participants completed the Autism Quotient, Schizotypal Personality Questionnaire, a Video Game Usage questionnaires, and two neurophysiological tasks. We tested in particular the hypotheses, motivated by previous work, that: (1) participants with higher autism scores would play video games more, and participants with higher schizotypy scores would play video games less; and (2) autism and positive schizotypy would be associated with opposite patterns of video game use, preferences and motivations. Females, but not males, with higher autism scores played more video games, and exhibited evidence of relatively male-typical video game genre preferences and motivations. By contrast, positive schizotypy was associated with reduced video game use in both sexes, for several measures of game use frequency. In line with previous findings, males played video game more than females did overall, preferred action video games, and exhibited faster reaction and targeting times. Females preferred Puzzle and Social Simulation games. Faster reaction and targeting times were associated with gaming motives related to skill development and building behavior. These findings show that gaming use and patterns reflect aspects of psychology, and gender, related to social cognition and imagination, as well as aspects of neurophysiology. More generally, the results suggest that video game use is notably affected by levels of autistic and schizotypal traits, and that video games may provide an evolutionarily-novel medium for imaginative play in which immersive play experiences can be decoupled from social interaction.